2018
DOI: 10.1002/jts.22296
|View full text |Cite
|
Sign up to set email alerts
|

Observed Emotional Expressivity, Posttraumatic Stress Disorder Symptoms, and Intimate Partner Violence Perpetration Among Community Couples

Abstract: Impaired emotional processes are related to posttraumatic stress disorder (PTSD) and are implicated in intimate partner violence (IPV) perpetration. To address the interpersonal context of PTSD, emotion, and IPV, we examined interactions among one's own and one's partner's emotional expressivity and PTSD symptom severity in association with IPV perpetration. Heterosexual couples (N = 56) in which at least one partner met screening criteria for PTSD engaged in two video-recorded discussions about negative and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 36 publications
2
6
0
Order By: Relevance
“…The present study showed that BC patients who used more negative emotional words reported lower levels of QOL over time, which is supported by Niles et al (2016), who identified that negative emotional word use was significantly positively correlated with increased depression. Sullivan, Leifker, and Marshall (2018) found that men's posttraumatic stress disorder symptom severity was associated with the expressivity of negative emotions. Our findings are also in accordance with the results by Pennebaker and Chung (2007), who reported that very high negative word use was associated with less benefit from EW.…”
Section: Discussionmentioning
confidence: 99%
“…The present study showed that BC patients who used more negative emotional words reported lower levels of QOL over time, which is supported by Niles et al (2016), who identified that negative emotional word use was significantly positively correlated with increased depression. Sullivan, Leifker, and Marshall (2018) found that men's posttraumatic stress disorder symptom severity was associated with the expressivity of negative emotions. Our findings are also in accordance with the results by Pennebaker and Chung (2007), who reported that very high negative word use was associated with less benefit from EW.…”
Section: Discussionmentioning
confidence: 99%
“…By expressing emotion, people assert their needs, feelings, and able to shape the environment. Previous study reveals that abused women who express emotions more, especially positive emotions, reported lower PTSD symptoms [8]. Expressing emotions also correlated to happiness and satisfaction in daily activities [9].…”
Section: Introductionmentioning
confidence: 85%
“…Human observers have also been used to measure how emotionally expressive a person appears to be within a given interaction Figure 1: Example frames from the GFT database [36,57]. However, these studies did not explore which specific behavioral signals the observers used to make their ratings.…”
Section: Emotional Expressivenessmentioning
confidence: 99%